Pancreatic pseudocyst development due to organophosphate poisoning - M. M. Murat HARPUTLUOĞLU; Ulvi DEMİREL and Hakan ALAN and Fehmi ATEŞ and Murat ALADAĞ and Melih KARINCAOGLU and Fatih HİLMİOĞLU (Turkish Journal of Gastroenterology, 2019)
-